Contamination of multiuse eyedrop bottles by exhaled air from patients wearing face masks during the COVID-19 pandemic: Schlieren imaging analysis. Issue 9 (September 2021) - Garcia, Giancarlo A.; Hines, Jacob A.; Wang, Evan W.; Davila, Jose R.; Chiang, Bryce; Choi, Daniel Y.
Abstract : Exposure of multiuse eyedrop bottles to exhaled air by patients occurs with use of recommended face masks but is significantly reduced by manual occlusion of the superior mask gap. Abstract : Purpose: To determine whether mask-induced redirected exhaled air through the superior mask gap contacts multiuse eyedrop bottles during drop administration and the efficacy of interventions to reduce such exposure. Setting: Academic ophthalmology center. Design: Interventional analysis. Methods: Schlieren airflow imaging was taken of an examinee wearing frequently used face masks and enacting common clinical scenarios—with and without manual occlusion of the superior mask gap and/or neck extension—and maximum visible vertical breath plume height was quantified. Bottle height during eyedrop administration was measured for 4 ophthalmologists during instillation to 8 eyes of 4 subjects. Results: Breath plume height (mean ± SD 275.5 ± 16.3 mm) was significantly greater than mean bottle height (13.9 ± 4.7 mm; P < .01). Plume height was reduced with manual mask occlusion vs without ( P < .01) and was also lower than mean bottle height with manual mask occlusion ( P < .01) but not in the absence of occlusion ( P < .01). Neck extension alone did not adequately redirect liberated breath to prevent contact with a bottle. Conclusions: Exhaled air liberated from commonly worn patient face masks was able to contact multiuse eyedrop bottles during eyedrop administration. These findings have important patient safety implications during the coronavirus disease 2019 pandemic and with other respiratory pathogens because these multiuse bottles could potentially serve as vectors of disease. Occlusion of the superior mask gap significantly reduces breath contamination and should be strongly considered by eyecare providers during drop administration in eye clinics.